2011
DOI: 10.1159/000332058
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Deep Brain Stimulation in Parkinson’s Disease under Different Anesthetic Modalities: A Comparative Cohort Study

Abstract: Background: The efficacy and feasibility of bilateral subthalamic deep brain stimulation (STN-DBS) for Parkinson’s disease (PD) under general anesthesia (GA) has not been evaluated. Objective: We compared the outcome of patients under GA with those who were operated on under local anesthesia (LA). Material and Methods: Thirty-three patients were assigned to the GA group (desflurane) and 19 patients were assigned to the LA group. Microelectrode recording (MER) was performed in both groups. The surgical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 68 publications
2
54
1
Order By: Relevance
“…Regardless of PRN dosing interpretations, the trend is unchanged, with patients in both groups exhibiting a significant LEDD decrease. Previous studies comparing awake and asleep DBS for PD patients have shown similar reductions in levodopa equivalents between 3 and 6 months [6,8,13,14,15,16]. Lower doses of levodopa have been associated with a lower likelihood of having dyskinesias, wearing-off phenomenon, and motor complications [1,2,3].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Regardless of PRN dosing interpretations, the trend is unchanged, with patients in both groups exhibiting a significant LEDD decrease. Previous studies comparing awake and asleep DBS for PD patients have shown similar reductions in levodopa equivalents between 3 and 6 months [6,8,13,14,15,16]. Lower doses of levodopa have been associated with a lower likelihood of having dyskinesias, wearing-off phenomenon, and motor complications [1,2,3].…”
Section: Discussionmentioning
confidence: 90%
“…Testing performed during these awake, off-medication surgeries included microelectrode recording and test stimulation. Recently, with patients under general anesthesia, direct targeting of the STN using intraoperative magnetic resonance imaging (MRI) or computed tomography (CT) to guide DBS lead placement has been implemented at several institutions, including ours [5,6,7,8,9,10,11]. The availability of this surgical technique provides patients unwilling or unable to tolerate awake surgery with an alternative option for DBS lead placement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic may lead to a higher stimulation side effect during clinical follow-up. 5 In addition to determining the correlation between the STN topography and the characteristic signal, enhancing MER neuronal signals under conditioned general anesthesia might facilitate the improvement of DBS outcomes.…”
mentioning
confidence: 99%
“…During surgery, the patient's head is fixed on a stereotactic frame, and as they are off their usual medication, the discomfort of rigidity and tremor can be difficult to manage. Also, the natural anxiety surrounding a surgical procedure can make blood pressure difficult to control and preclude patient cooperation after a few hours, increasing the potential for intraoperative complications [7,8] such as respiratory problems or intracerebral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%